Brazil: "Que país é esse"? : music and power in Legião Urbana - Lessa, Ana C. (2011)
This thesis addresses, amongst other issues, the phenomenon of protest music with particular reference to Brazil within its pre- and post-dictatorship period. The time-frame being understood as that which finds its roots many decades prior to the 1964 so-called revolution – a de facto¬ military putsch – and comes to flower in the democratic moment of the 1980s and since. The focus will be, eventually, directed to one of the most celebrated Brazilian rock phenomena, the band Legião Urbana, the impact of which still resonates across the artistic, cultural and political scene in Brazil and beyond. In order to establish the context in which such a claim can be viable, the thesis explores the ideological and historical background to the emergence, on a national, and international, stage of something beyond the artistic and cultural ‘dependence’ seing before that period within Brazilian music.